The protective effect of serum antibodies in preventing SARS-CoV-2 virus entry into cardiac muscle - Kessler, M; Vojtíšek, T; Zeman, T; Krajsa, J; Srník, M; Dziedzinska, R; Šerý, O (Physiological research, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been associated with significant cardiovascular complications, including myocardial infection and pulmonary embolism. This study aims to elucidate the relationship between the presence of SARS-CoV-2 RNA in the myocardium of the left ventricle and the levels of IgG and IgM antibodies against the SARS-CoV-2 virus in deceased COVID-19 patients. We conducted a post-mortem examination on 91 individuals who succumbed to COVID-19-related complications. The presence of SARS-CoV-2 RNA in the myocardium of the left ventricle was analyzed reverse transcription real time PCR (RT-qPCR) (EliGene® COVID19 UKV/SAV RT kit, Elisabeth Pharmacon), and antibody levels in serum were analyzed by serological assays (VIDAS SARS-COV-2 IgM and VIDAS SARS-COV-2 IgG II tests, BioMérieux). Of the heart tissue samples, 44 % tested positive for SARS-CoV-2 RNA. Our findings indicate that any detectable level of IgG antibodies against SARS-CoV-2 reduces the risk of viral penetration into the myocardium by more than fourfold. Specifically, individuals with detectable levels of IgG and IgM antibodies exhibited a significantly reduced presence of SARS-CoV-2 RNA in cardiac tissues (p<0.0001 for IgG and p<0.001 for IgM). Notably, all patients who died from pulmonary embolism had elevated levels of IgG antibodies. The study underscores the protective role of IgG and IgM antibodies in preventing SARS-CoV-2 penetration into cardiac tissues. However, high antibody titers were associated with fatal outcomes such as pulmonary embolism, pointing to the intricate balance of immune response in COVID-19 pathology. Key words SARS-CoV-2, Antibody, IgG, IgM, Cardiac damage, qPCR, Pneumonia, Pulmonary embolism, Heart failure.
Keywords: Virus Internalization; senioři; senioři nad 80 let; imunoglobulin G; SARS-CoV-2; Middle Aged; mužské pohlaví; Immunoglobulin M; COVID-19; Antibodies, Viral; Adult; RNA, Viral; imunoglobulin M; Aged, 80 and over; Immunoglobulin G; internalizace viru; ženské pohlaví; myokard; Humans; Myocardium; lidé středního věku; protilátky virové; dospělí; Female; Aged; RNA virová; lidé; Male